Performance and emissions of a modified small engine operated on producer gas - Homdoung,N. (Elsevier Limited, 2015)
© 2015 Elsevier Ltd. All rights reserved. Existing agricultural biomass may be upgraded converted to a gaseous fuel via a downdraft gasifier for spark ignition engines. In this work, a 0.6 L, naturally aspirated single cylinder compression ignition engine was converted into a spark ignition engine and coupled to a 5 kW dynamometer. The conventional swirl combustion chamber was replaced by a cavity chamber. The effect of variable compression ratios between 9.7 and 17:1, and engine speeds between 1000 and 2000 rpm and loads between 20% and 100% of engine performance were investigated in terms of engine torque, power output, thermal efficiency, specific fuel consumption and emissions. It was found that the modified engine was able to operate well with producer gas at higher compression ratios than with gasoline. The brake thermal efficiency was lower than the original diesel engine at 11.3%. Maximum brake power was observed to be 3.17 kW, and the best BSFC of 0.74 kg/kWh was achieved. Maximum brake thermal efficiency of 23.9% was obtained. The smoke density of the engine was lower than the diesel engine, however, CO emission was higher with similar HC emission.